Determinan Faktor yang Mempengaruhi Prestasi Kerja Karyawan PT Aerofood Indonesia Unit Jakarta: (Determinant Factors Affecting Employee Performance at PT Aerofood Indonesia Unit Jakarta) - Reta Ayu Puji Lestari; Farida Farida (e-Journal Ekonomi Bisnis dan Akuntansi, 2023)
This study aims to determine the effect of communication, work discipline, and work culture on PT Aerofood Indonesia unit Jakarta employees' work performance. This study uses quantitative research with data collection methods using interview techniques, questionnaires, and literature studies that take samples from the total population. The researchers used SPSS ver 25.0 For Windows for this statistical analysis. The data processing was carried out with the SPSS (Statistical Package for The Social Science) ver 25.0 programs with a population of 73 employees. The sampling technique in this study used a saturated sampling technique, where all members of the population were sampled. Adjust R Square with multiple determination is 61.4% and the remaining 38.6% is the contribution of other factors. For multiple linear regression values, = 2.271 + 0.328X1 + 0.349X2 + 0.250X3 and the F test with a calculated of 39.180 and Ftable 2.50 means F arithmetic > Ftable then H0 rejected and Ha accepted. This shows that Communication, Work Discipline, and Work Culture significantly affect Work Performance.